The influence of some motor abilities on the specific karate precision with hand and leg - Kostovski, Z.; Mikic, B.; Kostovska, V.; Zeljkovic, M.; Stankovic, N. (Sport Scientific and Practical Aspects - International Scientific Journal of Kinesiology, 2013)
The survey was conducted on the most quality karate athletes` cadets, members of representative selections of Macedonia. For this study were included a total of 31 karate experts (cadets) of the whole territory of the Republic of Macedonia. The main objective of the study was to determine the relations between the motor abilities, and the specific karate precision with hand and leg. The realization of this study was enabled with the measuring instruments that have satisfactory measurement characteristics, for assessment of: the basic motor skills (9 variables) divided by three measures in the specific motor spaces characteristics in karate sport (rhythmic structure, frequency of the segmented movements and explosive power of the lower limbs), represented as predictive system of the variables, and two (2 variables) to assess the specific karate precision with hand and leg, as criteria system of the variables. Using linear regression analysis, were determined the relations between the motor dimensions and the specific karate precision with hand.